Formação inicial de professores(as) de matemática: uma coreografia didática com os temas contemporâneos transversais - Costa, Muriell Francisco da (2023)
In this research, the central theme is the use of Contemporary Transversal Themes (TCT) applied to the development of pedagogical practices with future Mathematics teachers. The motivation for the study and application of TCT in the initial training of Mathematics teachers came from the observation and observation of educational learning in this formative stage, in which these students still have little knowledge about ways of working interdisciplinarity and/or transdisciplinary issues, debates, discussions and reflections on social issues that need to be part of the basic education curriculum. Motivated by this problem, it was investigated how a didactic choreography was constituted as a methodology of educational work in the remote modality for the use of Contemporary Transversal Themes by future mathematics teachers in the construction of digital authoring materials. This research is characterized by a qualitative approach, as it adopts ways in which the researcher sought to interpret the research object through perspectives that distanced from the empirical field, when considering the process of history and culture of each participant. The study involved the participation of five students in the seventh period of a degree course in Mathematics in the remote teaching modality, given the exceptionality of the pandemic caused by the COVID-19 virus, and had as instruments for collecting information observation, field notes, questionnaires, semi-structured interviews and the documents produced by students in the discipline who were enrolled during the period of this investigation. With the information collected, we sought to understand how the didactic choreography of this discipline was put into play for the training and educational process of these future mathematics teachers when working with TCT. With the methodological assumption of the Didactic Choreographies, four axes of analysis of this information were built, making it possible to understand the entire scenario of the research, namely: the anticipation of learning, demonstrating the identity and profile of the mathematics student, his/her digital culture and the relations of its history with TCT; the placement on the scene, presented the structuring, organization and developments of the discipline in research; the learnings, which analyzed and interpreted the learnings obtained with the creation of the digital copyright materials produced by the students through base models of learning with the TCT and the products, which presented the evaluation of the students' learning and describing, through the De model Kolb, what are the students' learning styles when developing the tasks proposed in the discipline. As a result of exposing the didactic choreography of TCT in the initial training of mathematics teachers, the final considerations of this investigation expose that, 1) the student's history implies the movement of their learning, 2) the need for care when organizing disciplines of a practical nature in higher education degree courses, 3) students' different learning styles produce an educational plurality in academic training and 4) the TCT propose to innovate the degree course curriculum through the relationship of three paths discovered in the research: the (in)fluence of digital technologies, the production of didactic knowledge and the knowledge that TCT consolidates when teaching and learning mathematics.